„Koncept” oraz „koncept literacki” w ujęciu konceptologicznym - Makarowska, Olga (Studia Rossica Posnaniensia, 2013)
This article is an attempt to organize the terminological apparatus of conceptology due to a large number of terms containing the word ‘concept’. The article presents a discussion of the differences and similarities between the terms concept and literary concept as well as the model structure of a literary concept.